1999
DOI: 10.1021/ja992188w
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid Mediated Hydrosilylation on Porous Silicon Surfaces

Abstract: Lewis acid mediated hydrosilylation of alkynes and alkenes on non-oxidized hydride-terminated porous silicon derivatizes the surface with alkenyl and alkyl functionalities, respectively. A very broad range of chemical groups may be incorporated, allowing for tailoring of the interfacial characteristics of the material. The reaction is shown to protect and stabilize porous silicon surfaces from atmospheric or direct chemical attack without compromising its valuable material properties such as high porosity, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
306
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(317 citation statements)
references
References 50 publications
10
306
1
Order By: Relevance
“…A well-established functionalization approach for the derivatization of hydride-terminated porous silicon (PSi) 186,187 is the Lewis acid-mediated (e.g. AlEtCl 2 ) attachment of olefins and acetylenes.…”
Section: Lewis Acid-catalyzed Hydrosilylation Reactionsmentioning
confidence: 99%
“…A well-established functionalization approach for the derivatization of hydride-terminated porous silicon (PSi) 186,187 is the Lewis acid-mediated (e.g. AlEtCl 2 ) attachment of olefins and acetylenes.…”
Section: Lewis Acid-catalyzed Hydrosilylation Reactionsmentioning
confidence: 99%
“…They also have the advantage of direct compatibility with organic materials via the strong and stable Si-C bond, providing a larger degree of freedom and flexibility in possible surface passivations and functionalities. [3][4][5][6][7][40][41][42][43] For example, it was recently demonstrated that H-passivated Si-np can be directly functionalized through a Si-C linkage terminating with a carboxylic acid group toward the solvent. This modification preserves the strong PL of the Si core, adds a hydrophilic interface for stability in aqueous media, and is easily reacted with primary amines to label biomolecules, all while adding only a small amount to the overall size.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis has generally focused on the source of PL and the debate between the quantum confinement (delocalized) and surface state (localized) mechanisms. Researchers studying porous Si structures, [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] for example, have attributed the PL to various sources ranging from quantum-confined nanorods and nanodots [44][45][46] to surface state silanone and siloxane groups. [47][48][49][50][51][52][53][54][55][56] For Si and Ge nanoparticles prepared through various routes such as solution-phase synthesis, [1][2][3][4][8][9] electrochemical etching, 10-13 laser ablation, 14,15 and using supercritical fluids, [16][17][18] the suggested PL sources have ranged from delocalized quantum confinement states 15 to localized SiSi surface dimer states.…”
Section: Introductionmentioning
confidence: 99%
“…Alkylpassivation is thought to have negligible effects on the photophysical properties of the Si domains, similar to hydride-passivation. 76 To this end, experimental evidence suggests that the Si NP surface can undergo alkyl-passivation as a means to preserve interband PL. 9 Consequently, numerous methods have been developed to form stable, Si-C passivated surfaces.…”
Section: Surface Defect Prevention In Silicon Nanoparticlesmentioning
confidence: 99%
“…76,79,80 For example, reaction of hydride-passivated porous silicon surfaces with terminal alkenes and alkynes in the presence of catalytic amounts of EtAlCl 2 was shown to form stable Si-C bonding at room temperature. 80 In that study, the authors reported a maximum reaction efficiency of 28 % when hydrosilylation was conducted with terminal alkenes, which was determined by calculating the percent decrease in the integrated intensity of the Si-H bond at 2100 cm -1 , as monitored by infrared (IR) spectroscopy.…”
Section: Si H + Simentioning
confidence: 99%